Hematopoietic SCT in Europe: data and trends in 2011 - Passweg, Jakob R.; Baldomero, H.; Bregni, M.; Cesaro, S.; Dreger, Peter; Duarte, R. F.; Falkenburg, J. H. F.; Kröger, N.; Farge-Bancel, D.; Bobby Gaspar, H.; Marsh, J.; Mohty, M.; et al. (Bone marrow transplantation, 2013)
In all, 651 from 680 centers in 48 countries reported 35 660 hematopoietic SCT (HSCT) in 32 075 patients (13 470 allogeneic (42%), 18 605 autologous (58%)) to the 2011 survey. Main indications were: leukemias; 10 113 (32%; 94% allogeneic); lymphoid neoplasias; non-Hodgkin’s lymphoma, Hodgkin’s lymphoma, plasma cell disorders; 18 433 (57%; 12% allogeneic); solid tumours; 1573 (5%; 5% allogeneic); and non-malignant disorders; 1830 (6%; 92% allogeneic). There were more unrelated donors than HLA identical sibling donors (54% versus 39%); proportion of peripheral blood as stem cell source was 99% for autologous and 73% for allogeneic HSCT. Cord blood was only used in allogeneic transplants (6% of total). In the past 10 years, the overall number of transplants has increased by 53%. Allogeneic HSCT have doubled (from 7272 to 14 549) while, autologous have increased by 32% and continue to increase by about 1100 HSCT per year since 2001. In the past 2 years, an increase of >2000 HSCT per year was seen. Transplant activity is shown by team size. For allogeneic HSCT, we show use of reduced-intensity conditioning versus myeloablative conditioning across Europe and use of post-transplant donor lymphocyte infusions with considerable variation across different countries.
Gesehen am 20.12.2021